Maintenance and functionality of memory B cell responses during dengue infection - Ng, Irene Hai Ying (2019)
Dengue virus (DENV) is an increasing global burden with approximately 390 million infections occurring annually. Humoral immunity is important in rapidly neutralising DENV in repeated infections. Due to the presence of four DENV serotypes, neutralising antibodies may not be as potent in subsequent heterologous DENV infections, resulting in increased disease severity. However, little is known about the maintenance of DENV-specific memory B cells (MBCs) and the affinity of its antibodies during dengue infection. Therefore, this study aims to analyse the maintenance and functionality of MBC responses during different time points following infection. The analysis of the MBC maintenance was conducted using fluorospot assay and the affinity of antibodies using affinity assay and DENV-specific enzyme-linked immunosorbent assay. Frequencies of DENV-specific MBCs were not maintained after 7 months post-DENV infection, although a small percentage was still detectable at 12 months time point. Furthermore, serotype cross-reactive MBCs could be present even after 1-year post-DENV infection. Although the affinity of DENV-specific antibodies was inconclusive for some donors, possible correlation between the frequency of MBCs and affinity of its antibodies secreted was suggested in other donors. Follow-up studies should be conducted with increased sample size to gain further insights to long-term immunity against DENV.